2007
DOI: 10.1080/01900690701225606
|View full text |Cite
|
Sign up to set email alerts
|

Governors and the Bureaucracy: Executive Resources as Sources of Administrative Influence

Abstract: Recent years have marked the advent of a variety of institutional mechanisms designed to enhance governors' capacity to oversee the bureaucracy. In many states, more traditional gubernatorial resources have also been bolstered. This study evaluates the effectiveness of these tools in influencing the policy activities of state agencies. We find that, in general, these resources significantly increase the amount of gubernatorial influence reported by state administrators. Our evidence suggests that institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The utility of procedural controls as a mechanism for political influence is a matter of some dispute. Although some statistical analyses of agency behavior have found that procedural requirements are correlated with increased political influence (Potoski & Woods 2001;Woods & Baranowski 2007;Woods 2009) and may affect policy outcomes (Woods 2015) others have found such effects to be temporary, limited, or nonexistent (Spence 1999a;Hedge & Johnson 2002;Shapiro & Borie-Holtz 2013). Case studies suggest that the latter result may occur because agencies adapt to the procedural requirements in ways that serve to minimize their policy effects.…”
Section: Evaluating the Effects Of Regulatory Analysis Proceduresmentioning
confidence: 99%
“…The utility of procedural controls as a mechanism for political influence is a matter of some dispute. Although some statistical analyses of agency behavior have found that procedural requirements are correlated with increased political influence (Potoski & Woods 2001;Woods & Baranowski 2007;Woods 2009) and may affect policy outcomes (Woods 2015) others have found such effects to be temporary, limited, or nonexistent (Spence 1999a;Hedge & Johnson 2002;Shapiro & Borie-Holtz 2013). Case studies suggest that the latter result may occur because agencies adapt to the procedural requirements in ways that serve to minimize their policy effects.…”
Section: Evaluating the Effects Of Regulatory Analysis Proceduresmentioning
confidence: 99%
“…During the waves of executive branch reorganization, the number of states that utilized a cabinet system of government increased from 26 to 40 between 1969 and 1982 (Beyle and Muchmore 1983, 13). The cabinet system greatly concentrates executive power because a governor’s influence over the executive branch is closely tied to her control of the selection of executive branch officers (Brudney and Hebert 1987; Conant 1988; Garnett 1980; Woods and Baranowski 2007). Conversely, state executive officials that are elected (or appointed by someone other than the state executive) have a base of power independent from the governor.…”
Section: State Executive Branch and Gubernatorial Powermentioning
confidence: 99%
“…Executives possess many formal tools that affect their ability to influence executive branch activity and policy outcomes. Executive means of bureaucratic control include appointment power, rule review, budgetary control, and the ability to reorganize executive branch structures (Lewis 2005; Wiseman 2009; Woods and Baranowski 2007). The U.S. states provide an ideal setting to examine how variation in executive control influences judicial decision-making.…”
mentioning
confidence: 99%
“…The formal barriers to influence are more or less permeable. Politicians, at various jurisdictional levels have a wide range of indirect methods to try and permeate, circumvent, or simply overpower formal ownership structure barriers to influence [133][134][135]. There is evidence, for example, that U.S. state-level politicians have gained considerable influence over federal agencies even though they have no formal authority over them [136][137][138].…”
Section: Political Influence Barriersmentioning
confidence: 99%